Analysis of Sales Forecasting on Galah Kopi Using the Fuzzy Time Series Method - Purnama Yanti, Christina; Setya Devi, Kadek Listy Mas; Murpratiwi, Santi Ika; Hendrawati, Theresia (Journal of Electrical, Electronics and Informatics, 2023)
Galah Kopi is one of the coffee shops in Tabanan. Addressed at Jl. Raya Babadan Senganan No. 13, Penebel District, Tabanan Regency. Galah Kopi's sales only use previous sales data as a benchmark without the aid of calculations using a more accurate scientific method. The coffee shop also experienced erratic sales problems. The solution that can be used is to do forecasting. This study uses the Fuzzy Time Series method for sales forecasting. The results of this study show that the model method has an accuracy value where the results of the coffee category with an MSE value of 901,917, MAE 27,715 and MAPE 6,115, the Chen model with an MSE value of 4939,505, MAE 57,952 and MAPE 12,574. Fuzzy time series model Singh in the non-coffee category with MSE values ??of 3249.019, MAE 50.177 and MAPE 6.96, with the Chen model with MSE values ??of 23536.2, MAE 125.904 and MAPE 19.00. Fuzzy time series model Singh for the Food category with MSE values ??of 1286.453, MAE 32.187 and MAPE 8.211, with the Chen model with MSE values ??of 14175.61, MAE 98.273 and MAPE 103.45. Fuzzy Time Series Singh model in snack category with MSE value of 1285.114, MAE 30.845 and MAPE 41.967, with the Chen model with MSE value of 14175.61, MAE 98.273 and MAPE 103.45. So that the model method that has the smallest accuracy is the fuzzy time series Singh